Regulatory T cells and T‐cell‐derived IL‐10 interfere with effective anti‐cytomegalovirus immune response. Issue 10 (29th July 2014) - Jost, Nils H; Abel, Simone; Hutzler, Marina; Sparwasser, Tim; Zimmermann, Albert; Roers, Axel; Müller, Werner; Klopfleisch, Robert; Hengel, Hartmut; Westendorf, Astrid M; Buer, Jan; Hansen, Wiebke
Abstract : Cytomegalovirus (CMV) establishes lifelong chronic infection in its host with mostly asymptomatic or only mild disease, but under immunosuppressive conditions the virus can reactivate and infection can cause life‐threatening disease. CMV has evolved several mechanisms to escape from host's immunity, allowing persistence of the virus. Until now, it remains elusive whether regulatory T cells (Tregs) have an impact on insufficient host immune response against the virus in this context. In the present study, we provide evidence that CD4 + Foxp3 + naturally occurring Tregs (nTregs) as well as CD4 + Foxp3 − IL‐10 + ‐induced Tregs (iTregs) interfere with an effective anti‐mouse CMV (mCMV) immune response. Depletion of Foxp3 + Tregs by using DEREG mice resulted in enhanced T‐cell activation as measured by the expression of CD62L, granzyme B and interferon (IFN)‐γ and was associated with reduced viral titers in salivary glands, the organ where mCMV mainly persists. Moreover, we identified CD4 + Foxp3 − T cells to produce elevated levels of the immunosuppressive cytokine IL‐10 at early time points during mCMV infection. Analysis of T‐cell activation and viral replication in mCMV‐infected IL‐10 flox/flox × CD4‐cre mice and IL‐10 flox/flox × FIC mice revealed that T‐cell‐specific inactivation of IL‐10, but not Foxp3 + Treg‐specific IL‐10 ablation alone, resulted in elevated IFN‐γ production by T cells associated with a significant decrease in viral loads in salivary glands. Thus, our data illustrate a crucial role for CD4 + Foxp3 + nTregs as well as IL‐10‐producing CD4 + Foxp3 − iTregs in the regulation of appropriate T‐cell responses and viral clearance during mCMV infection.